RANCANG BANGUN DATA WAREHOUSE UNTUK ANALISIS STRATEGI PRODUKSI PENJUALAN USULAN : PT.XYZ - Rahmad Syah (Teknik Informatika Universitas Malikussaleh, 2014)
Some companies convection that is often experienced by the owner of XYZ lies in the lack of information provided by each - each branch office ( lack of synchronization between the data center and branch office ). This is because the human resources available in each - each branch office is not sufficient to be able to make a more detailed report to the center. Inadequate reports of each - each branch office , also led to the management does not know for sure about their finances and inventory - each branch . System to be built is a container used to store data from various branch offices . Of these containers will be carried out such ananalysis process OLAP ( OnLine Analytical Processing ) and can also be used as reporting tools .Operational data of each branch will be entered into a central database . After that , we will perform an Extraction , Transformation , and Loading to filter the data that will be inserted into the data warehouse . Modeling the model used is the Star . Architecture that will be used is Two - Layer Architecture . The information generated from the processing of the data warehouse design waking with OLAP analysis in the form of a query . Information presented in the form of queries : goods , office and date